A STUDY ON THE CHANGES OF PERSPECTIVE ON DISCRIMINATION AMONG IN-GROUP PEERS IN ROMANIAN SCHOOLS - Enachi-Vasluianu, Luiza; Malureanu, Flavia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Even if most of modern schools today value diversity, promote multiculturalism, enforce antiharassment policies, they still confront with discrimination and its negative effects. Irrespective of teachers’ efforts to stop this phenomenon, discrimination will always manifest within classrooms through less or more aggressive forms as children have a tendency to reject what is different as a form of self-protection.The specific focus of this article is on different types of discrimination of in-group peers at gymnasium and high school. The two levels of school were selected as at these ages (11-15 for gymnasium and 15-19 for high school) students possess the cognitive and emotional capacities to deal with such experiences. The investigations performed led to the  identification of discrimination based on social categories, financial conditions, ethnicity (mutual discrimination between Romanians and Gypsies/Roma), environment of provenance (rural versus urban areas), physical or mental disability, religion (the sample involved in the research are mostly orthodox, but there are also confessions with differences in religious beliefs and practice).The present study has as starting point a research done in 2007, which put under the lens the main types of discrimination existing within classroom groups of peers from gymnasium and high school. The study was resumed in 2019 using the same criteria of investigation. We compared the two series of data and the results reflect the differences of students’ perspectives on the same types of discrimination investigated at 12 years distance in time. As research methods we used the investigation based on questionnaire, the conversation and the systematic observation. The data gathered were processed using the SPSS analysis. The results of the research could be used to establish strategies of antidiscrimination based on respect and tolerance for diversity.